And Grandfather died (Journal of Parents and Teachers, 2026)
The collection of anecdotes and memories from children about theirgrandparents reflects how they perceive their presence, affection, and teachings. Theseanecdotes reflect the emotional importance of grandparents. Even after their death, wecan see how grandparents influence the formation of values, habits, and the happiestmemories of children.
Keywords: Grandparents, Childhood, Family, and Memories